Pengaruh Sektor Pariwisata, Produk Domestik Regional Bruto (Pdrb), Tingkat Investasi Dan Jumlah Penduduk Terhadap Peningkatan Pendapatan Asli Daerah (Pad) Tahun 2010-2014 (Studi Kasus Kabupaten/Kota Eks Karesidenan Surakarta) - Kamila, Aisyah; , Dr. Erma Setiawati, MM.,CA (2016)
Intention of this research is to know and analyses influence of tourism sector, gross regional of domestic product (PDRB), investment level, amount of resident to make-up of earnings of area genuine (PAD) inex region of Karesidenan Surakarta. This research use quantitative method by using data of secondary obtained of statistical center body (BPS) and also relevant institutions. Population in this research is all sub-province/city of ex region of Karesidenan Surakarta. Amount of sample in this research is seven of area during five year. Method gathering of sample used purposive sampling technique. Used analyzer which covering of normality test, multycolinierity test, heteroskedastisity test, doubled linear regression analyses, F test, determinescoefficient of R2 test, and t test. Pursuant to result of data analysis can be concluded that tourism sector variable do not have an effect on to earnings of area genuine, because tcalculated (- 1,185) < ttable (2,045) with level of significant equal to 0,245 > (0,05). While gross regional of domestic product variable have an effect on to earnings of area genuine, because tcalculated (2,569) > ttable (2,045) with level of significant equal to 0,015 < (0,05). Then at mount investment level variable have an effect on to earnings of area genuine, because tcalculated (2,561) > ttable (2,045) with level of significant equal to 0,016 < (0,05). Hereinafter the amount of resident have an effect on to earnings of area genuine, because tcalculated (- 2,371) >ttable (2,045) with level of significant equal to 0,041 < (0,05). And so it is with test accuracy of model (simultan) show result of statistical test of distribution of Fcalculated> Ftable that is 21,216 > 2,55 with value probability smaller than level of significance research of 5%, that is equal to 0,000. Adjusted R2 equal to its 0,704 meaning of tourism sector, gross regional of domestic product, investment level and resident amount can explain earnings of area genuine variability equal to 70,4%.